A Novel Metastable Pentavalent Plutonium Solid Phase on the Pathway from Aqueous Plutonium(VI) to PuO2 Nanoparticles. (6th November 2019) - Kvashnina, Kristina O.; Romanchuk, Anna Yu.; Pidchenko, Ivan; Amidani, Lucia; Gerber, Evgeny; Trigub, Alexander; Rossberg, Andre; Weiss, Stephan; Popa, Karin; Walter, Olaf; Caciuffo, Roberto; Scheinost, Andreas C.; et al.
Abstract: Here we provide evidence that the formation of PuO2 nanoparticles from oxidized Pu VI under alkaline conditions proceeds through the formation of an intermediate Pu V solid phase, similar to NH4 PuO2 CO3, which is stable over a period of several months. For the first time, state‐of‐the‐art experiments at Pu M4 and at L3 absorption edges combined with theoretical calculations unambiguously allow to determine the oxidation state and the local structure of this intermediate phase. Abstract : Aus fester Überzeugung : Die Bildung einer neuartigen festen Phase von pentavalentem Plutonium wurde auf dem Reaktionspfad von wässrigem Pu VI zu PuO2 ‐Nanopartikeln beobachtet. Die Untersuchungen wurden mittels Fluoreszenzdetektion mit hoher Energieauflösung an den M4 ‐ und L3 ‐Kanten von Pu sowie Berechnungen der Elektronenstruktur durchgeführt.